A new Hyalella species (Crustacea: Amphipoda: Hyalellidae) from South American Highlands (Argentina) with comments on its cuticular ultrastructure - Verónica, Isa Miranda Águeda; Alejandra, Peralta Marcela (Zootaxa, 2022)
Hyalella Smith, 1874 includes approximately 92 species present only in the Neotropical and Nearctic regions. Hyalella is a dominant taxon in Central Andean Highland wetlands of Northwestern Argentina. We describe a new Hyalella species from Chorrillos, a cold-hyperfresh Puna peatbog in Salta province. Two other species occur in the Puna biogeographic province, namely H. kochi González & Watling, 2001 and H. puna Peralta & Isa Miranda, 2019. The new species differs from H. puna mainly in having a smooth body surface; propodus of male gnathopod 1 hatchet-shaped, with nine serrate setae on inner margin; uropod 3 peduncle with two strong distal setae; and number and distribution of telson setae; from H. kochi by having the male uropod 1 without modified curved seta on inner ramus; six sternal gills on pereionites II-VII; globose peduncle of uropod 3 with two strong distal setae; long palp of maxilla 1. We also compared its external morphology with that of H. fossamancinii Cavalieri, 1959, another species recorded in the High Andes. We contribute new details on ultrastructural morphology of cuticular extensions (setae; microtrichs; denticles and pores). With this new species, the number of known Hyalella species in Argentina and Falkland Islands (Islas Malvinas) rises to 13.